2016
DOI: 10.21653/tfrd.286776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weighted Versus Standard Jump Rope Training on Physical Fitness in Adolescent Female Volleyball Players: A Randomized Controlled Trial

Abstract: Purpose: The aim of this study was to compare the effects of 12-week standard versus weighted jump rope training on physical fitness tests including anaerobic power, speed, agility and flexibility in female adolescent volleyball players.Methods: Twenty-five female volleyball players were recruited to the study. Participants were randomly separated into three study groups; weighted jump rope training (n=8), standard jump rope training (n=9) and control group (n=8). All participants were assessed at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…The participants of these two studies were female youth volleyball players. One study was a cohort study with a 12-week intervention period [43], and the other was a randomized controlled trial which also had an intervention period of 12 weeks [45]. The results of these studies reveal that plyometric training can improve flexibility by 9% [43] to 14% [45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants of these two studies were female youth volleyball players. One study was a cohort study with a 12-week intervention period [43], and the other was a randomized controlled trial which also had an intervention period of 12 weeks [45]. The results of these studies reveal that plyometric training can improve flexibility by 9% [43] to 14% [45].…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review found three studies which observed the effects of plyometric training on the agility/speed of volleyball players [43,46,47]. The results can be found in Table 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the study, 20-m speed values were significantly lower in the rope-jump group than in the control group (p<0.05). Turgut et al (2016) conducted a study on adolescent volleyball players, and determined that there were significant increases in the anaerobic strength and speed values of the study group when compared with the control group after a 12-week rope and weighted-rope trainings [23]. Endo et al (2007) reported that when the rope-jump was used in an efficient way in the growth attack period between 9 and 13 age group, the sprint performance values increased [24].…”
Section: Discussionmentioning
confidence: 99%
“…Düzgün et al (2010) conducted a study on adolescent volleyball players, and reported that weighted-rope-jump training programs increased the shoulder (scapula) outer rotation strength levels [27]. Turgut et al (2016) conducted a study on adolescent volleyball players and reported that Rope-Jump trainings provided advantage in strength and agility [23]. As a result of 12-week rope and weighted-rope trainings, significant increases were determined in the anaerobic strength and speed values in the weighted-rope-jump group when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%